AB0456 Safety and retention rate of belimumab: data from a multicentric italian study. (15th June 2017) - Iaccarino, L; Larosa, M; Andreoli, L; Bartoloni-Bocci, E; Bortoluzzi, A; Ceccarelli, F; Conti, F; Angelis, R De; Marchi, G De; Vita, S De; Matteo, A Di; Emmi, G; et al.
Abstract : Background: Belimumab is used in the treatment of systemic lupus erithematosus (SLE), but few data on its safety in daily clinical practice are available to date. Objectives: To investigate safety, retention rate (RR), reasons and predictors of belimumab discontinuation in a prospective multicentric Italian study. Methods: A total of 188 active SLE patients refractory to standard therapy were treated with belimumab as add-on-therapy in 11 Italian centers. Adverse events (AEs) were defined as "any untoward medical occurrence in a patient treated with a pharmaceutical product which does not necessarily have a causal relationship with this treatment". AEs were subdivided in non-infectious, infectious, infusion and hypersensitivity reactions. Infusion and hypersensitivity reactions were defined as transient AEs related to belimumab occurring within 6 hours and 6–48 hours after drug administration, respectively. AEs was defined as severe (SAE) in case of hospitalization and/or death and/or life-threatening manifestations. Infections were considered severe in case of hospitalization and/or intravenous antibiotic use and/or death. Infusion and hypersensitivity reactions were considered severe when intensive care unit support was required. As baseline predictors of discontinuation the following variables were analyzed: gender, age, age at SLE onset, disease duration, disease activity pattern (relapsing remitting or chronic active), SLEDAI-2K ≥10, prednisone >7.5 mg/day, concomitant immunosuppressant, antimalarial drug use, number and type of comorbidities, number of previous organ involvement, type of major involvement and number of flares in the 12 months before belimumab initiation. Data were analyzed using the SPSS (version 23.0, Chicago, IL) software. Results: A total of 453 EAs were recorded in 132 patients after a mean follow-up period of 17.5±10.6 months (range 3–36): 443 (97.8%) were non severe and 10 (2.2%) SAEs (Table 1 ). No deaths and severe infusion/hypersensitivity reactions occurred. Belimumab discontinuation was observed in 58 patients (30.8%) after 10.4±7.5 months of follow-up (Table 2). RR was 91.5% at 6 months, 81.4% at 12 months, 72.9% at 18 months, 72.4% at 24 months, 69.7% at 30 months and 69.2% at 36 months. No associations were found between baseline variables and drug discontinuation. Conclusions: Belimumab demonstrated a good safety profile with a low rate of SAEs. Discontinuation occurred in less than 1/3 of subjects with a low rate of discontinuation due to AEs. Disclosure of Interest: None declared